Design of a CH3NH3PbI3/CsPbI3-based bilayer solar cell using device simulation. Issue 7 (July 2022) - Khatoon, Sidra; Yadav, Satish Kumar; Singh, Jyotsna; Singh, Rajendra Bahadur
Abstract: With lead-based light harvesters, perovskite solar cells (PSCs) have an efficiency of approximately 25.5%, making them a viable photovoltaic technology. The selection of the absorber materials for PSC in this work are (i) Cesium lead iodide (CsPbI3 ) with a 1.73eV bandgap as the first absorber layer, this halide imparts higher stability to perovskite solar cells (ii) CH3 NH3 PbI3 (MAPbI3 ) with a bandgap of 1.55eV is selected as the second absorber layer as this material provides better efficiency to the perovskite solar cells. SCAPS-1D simulation software is used to perform an efficiency analysis of perovskite-perovskite CsPbI3 /MAPbI3 bilayer solar cell. For efficiency optimization of the perovskite-perovskite bilayer solar cell, we have tried to calibrate seven parameters of the cell. These parameters are (i & ii) selection of the electron and hole transport material (iii, iv & v) variation in the: defect density of bulk material, doping concentration and the thickness of absorber layers, (vi) variation in work function of front electrode (vii) varying interface defect density. After optimization, the efficiency (η) of bilayer PSC is estimated to be 33.54%. The other PV parameters observed in optimal efficiency condition are open-circuit voltage (VOC ) = 1.34V, short-circuit current density (JSC ) = 27.45 mA/cm 2 and fill factor (FF) = 90.49%. The CsPbI3 /MAPbI3 bilayer perovskite solar cell efficiency is roughly double the efficiency of single junction CsPbI3 or MAPbI3 PSC. Our analysis observed that the variation in the doping and defect density of narrow bandgap material profoundly impacts the efficiency of perovskite-perovskite bilayer solar cells compared to the wide bandgap material. Abstract : Bilayer solar cell, Efficiency, Photovoltaic performance, Thickness.